CARBONIFEROUS-PERMIAN BOUNDARY AS INDICATED BY CONODONTS - Barskov I.S.; Reimers A.N. (My University, 1996)
The analysis of successive conodont assemblages from Carboniferous-Permian boundary sediments of the Aidarlash and Usolka sections revealed that the boundary approaching that in the ammonoid standard is in the transition interval between the following species: Streptognathodus alius ⇒ barskovi; Str. simplex ⇒ asselicus; Str. elongatus ⇒ cristellaris; Str. elongatus ⇒ minacutus. Two key species Str. barskovi and Str. minacutus sp. nov. = Str. acuminatus Gunnell sensu Chernikh were redescribed. The phylogenetic relationships between Streptognathodus species in the designated interval were traced. Copyright © 1996 by MAEe cyrillic signK Hayκa/Interperiodica Publishing.
Keywords: Carboniferous; Permian; Палеозой::Каменноугольная; Paleozoic::Permian; Paleozoic::Carboniferous; Палеозой::Пермская